Exploring typical and atypical variants of celiac disease: a narrative review - Oza, Yugam R.; Hassan, Hussein Abdikadir; Joshi, Helly Mayankkumar; Siddiqui, Aisha; Siddiqui, Farina Fartima; Gul, Muhammad Hamza (International Journal of Research in Medical Sciences, 2023)
There are many different clinical manifestations of celiac disease (CD), including the classical form, in which intestinal symptomatology predominates on the contrary there is atypical forms, in which extra-intestinal clinical features predominate, and the silent form, in which there are no clinical symptoms. Few or no gastrointestinal symptoms and a predominance of extra-intestinal features, including liver, kidney, skeletal, psychiatric, neurologic, dermatologic, hematologic, endocrinological, and reproductive involvements, define the atypical forms of the disease. Through screening high-risk groups, silent presentations of CD may be found. It is crucial for healthcare professionals to have a high level of suspicion for the atypical presentations of CD because it is now well known that CD may account for a number of chronic health issues.